Dividing a Cake by Majority: The Simplest Equilibria - David Baron; Ehud Kalai (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
In a stochastic game of dividing a cake by majority, the simplest equilibria are the Baron-Ferejohn (1989) ones. The formal definition of simplicity and the computational methods of the equilibria make use of an automaton measure of complexity adopted for stochastic games.
Keywords: 330